2020
DOI: 10.1136/bmjopen-2020-042045
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and washing of cloth masks and risk of infection among hospital health workers in Vietnam: a post hoc analysis of a randomised controlled trial

Abstract: BackgroundIn a previous randomised controlled trial (RCT) in hospital healthcare workers (HCWs), cloth masks resulted in a higher risk of respiratory infections compared with medical masks. This was the only published RCT of cloth masks at the time of the COVID-19 pandemic.ObjectiveTo do a post hoc analysis of unpublished data on mask washing and mask contamination from the original RCT to further understand poor performance of the two-layered cotton cloth mask used by HCWs in that RCT.Setting14 secondary-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 11 publications
1
45
0
1
Order By: Relevance
“…There were still some participants (6.8%) who washed their masks after some days of use but less than a week or after every week of use. It is documented that a well-washed cloth mask can be as protective as a medical mask [ 25 ]. This makes proper washing of face mask a key requirement in ensuring the effectiveness of face mask [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were still some participants (6.8%) who washed their masks after some days of use but less than a week or after every week of use. It is documented that a well-washed cloth mask can be as protective as a medical mask [ 25 ]. This makes proper washing of face mask a key requirement in ensuring the effectiveness of face mask [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is documented that a well-washed cloth mask can be as protective as a medical mask [ 25 ]. This makes proper washing of face mask a key requirement in ensuring the effectiveness of face mask [ 24 , 25 ]. It is suggested that cloth mask should be washed appropriately in hot water and soap everyday [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloth masks made according to sound design principles, such as at least 3 layers, a water-resistant outer layer, good fit around the face may be as effective as a surgical mask (40). In addition, daily and adequate washing of cloth masks is required for effectiveness (41). Ensuring access to good quality cloth masks, avoiding low quality face coverings such as scarves or bandanas, and providing information on the best methods for making a high-quality mask will enhance protection.…”
Section: Discussionmentioning
confidence: 99%
“…Pri každodennom individuálnom praní (v 75 % pri ručnom praní) dvojvrstvových textilných rúšok bolo riziko nákazy dvojnásobne vyššie oproti jednorazovým chirurgickým rúškam. V prípade ich profesionálneho každodenného prania (60 -90 °C) boli oba typy rúšok porovnateľné (9).…”
Section: Rúško -Kedy Sa Ochranná Bariéra Mení Na Ohnisko Infekcie?unclassified